2019
DOI: 10.1107/s205979831901057x
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of the CAMP factor ofStreptococcus agalactiaewith the aid of an MBP tag and insights into membrane-surface attachment

Abstract: CAMP factor is a unique -helical bacterial toxin that is known for its cohemolytic activity in combination with staphylococcal sphingomyelinase. It was first discovered in the human pathogen Streptococcus agalactiae (also known as group B streptococcus), but homologous genes have been found in many other Gram-positive pathogens. In this study, the efforts that led to the determination of the first structure of a CAMP-family toxin are reported. Initially, it was possible to produce crystals of the native protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The CAMP factor, which is present in all GBS isolates, is encoded by the cfb gene. It has the property of lysing the membranes of erythrocytes that have been pre-treated with the β-hemolysin of Staphylococcus aureus, a sphingomyelinase [16].…”
Section: Introductionmentioning
confidence: 99%
“…The CAMP factor, which is present in all GBS isolates, is encoded by the cfb gene. It has the property of lysing the membranes of erythrocytes that have been pre-treated with the β-hemolysin of Staphylococcus aureus, a sphingomyelinase [16].…”
Section: Introductionmentioning
confidence: 99%
“…MBP tags can be easily detected by immunoassay Nosaki et al (2021) have successfully revealed the crystal structure of AtBIL1/ BZR1 DBD and target DNA complex by the combination of MBP-mediated crystallization and MD simulation. This is shown to be capable of deciphering the protein-DNA recognition code of interest Li et al (2019) found that MBP tag can assist in the crystallization of the CAMP factor of Streptococcus agalaciae, facilitating the subsequent study of the structure of the CAMP factor Guo et al (2018)used MBP tag to prepare high purity and high activity MBP-MLIF in the E. coli expression system. On the whole, this method has advantages such as simplicity and application, which promotes the scientific research of stem cells SUMO 11.2 kDa (Heinrich et al, 2019) It can increase the expression amount of the fusion proteins (Mohammadi et al, 2022), and has the functions such as anti-protease hydrolysis, promoting the correct folding of the target protein, enhancing the solubility, and shielding the toxic proteins Kim et al (2019) used SUMO tag and His tag to construct a new vector pKSEC1 for the production of antimicrobial peptide-Abaecin, providing a new scheme for the treatment of bacterial infection Mohammadi et al (2022) The carrier of affinity chromatography should have the following characteristics (Chen et al, 2003): 1) Insoluble in water, but highly hydrophilic; 2) Inert substance with good specificity; 3) There are enough chemical groups for activation; 4) Stable physical and chemical properties; 5) Good mechanical properties, with a certain particle shape to maintain a certain flow rate; 6) Good permeability, with porous network structure for free passage of macromolecular substances; 7) It can resist the damage to microorganisms and alcohols.…”
Section: Tags Sequence/size Features Applicationmentioning
confidence: 99%
“…Briefly, currently, understanding of the pathogenic impacts of CAMP includes its oligomerization to support forming discrete pores on host membranes and its binding to glycosylphosphatidylinositol (GPI)-anchored proteins, which can promote cell lysis [45]. Recently, two research groups identified the structure of CAMP, which provided more details about its perforating function [46,47]. Podbielski et al (1994) demonstrated that a full-sized recombinant CAMP-factor exerts co-hemolytic activity [42].…”
Section: Camp Factormentioning
confidence: 99%